Individual and family factors correlated with children’s fruit consumption - Wu, Xiangyi; Yu, Yingjie; He, Hairong; Yu, Xiaohui; Guo, Dandan; Zhu, Wenli (Frontiers in Public Health, 2024)
Background: Fruits are essential for health, yet their consumption in children is inadequate, with unclear influencing factors. Methods: A cross-sectional study was conducted among students in grades 3-12 in Beijing, China, from September 2020 to June 2021. Fruit consumption in children was surveyed using a self-administered food frequency questionnaire. Additionally, children's food and nutrition literacy and family food environments were assessed using the "Food and Nutrition Literacy Questionnaire for Chinese School-age Children" and the "Family Food Environment Questionnaire for Chinese School-age Children," respectively. Results: Out of 10,000 participating children, 62.5% consumed fruit daily, with a lower frequency among boys (59.3%) compared to girls (65.8%), and among senior students (48.6%) compared to junior (63.6%) and primary students (71.2%). Fruit consumption was positively associated with other healthy foods (vegetables, whole grains, etc.) and negatively with unhealthy foods (sugared soft drinks). Children with higher food and nutrition literacy consumed fruits daily more frequently (82.4% vs. 59.9%, ORs=2.438, 95%CI: 2.072-2.868). A significant positive correlation was found between children's fruit consumption and a healthy family food environment (66.4% vs. 50.2%, OR=1.507, 95%CI: 1.363-1.667). Conclusions: The results indicate that individual food and nutrition literacy and family food environment are key positive predictors of children's fruit consumption. Future interventions should focus on educating children and encouraging parents to foster supportive family environments.